2019
DOI: 10.1111/eve.13187
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the occurrence of, and risk factors for, concurrent suspensory ligament injuries in horses with hindlimb proximal suspensory desmopathy

Abstract: Hindlimb proximal suspensory desmopathy (PSD) is a common cause of lameness or poor performance in horses and may occur alone or together with other suspensory ligament (SL) injuries in forelimbs or hindlimbs. The aims of this retrospective case-control study (January 2009 to December 2018) were to describe the occurrence of, and identify risk factors for, concurrent SL injuries in horses with hindlimb PSD. Data concerning age, breed, sex, work discipline, height, bodyweight and work history were collected. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Equine studies have shown a potential relationship between obesity, or body weight:height ratio, with the development of orthopaedic problems. A linear relationship between CSA of SDFT and BMI was also reported for 6-year-old horses (Agut et al, 2009;Gruyaert et al, 2020). Another study investigated several risk factors for SDF tendinopathy Odds ratio (OR) and showed an increased OR with increasing body weight (≥470 kg) and also reported that risks of SDF tendinopathy in males and geldings were significantly higher than in females (Ikeda et al, 2019).…”
Section: Ta B L E 1 Mechanical Properties Of the Energy-storing (Supe...mentioning
confidence: 66%
“…Equine studies have shown a potential relationship between obesity, or body weight:height ratio, with the development of orthopaedic problems. A linear relationship between CSA of SDFT and BMI was also reported for 6-year-old horses (Agut et al, 2009;Gruyaert et al, 2020). Another study investigated several risk factors for SDF tendinopathy Odds ratio (OR) and showed an increased OR with increasing body weight (≥470 kg) and also reported that risks of SDF tendinopathy in males and geldings were significantly higher than in females (Ikeda et al, 2019).…”
Section: Ta B L E 1 Mechanical Properties Of the Energy-storing (Supe...mentioning
confidence: 66%
“…However, a predominance of left hindlimb lameness has previously been documented (Gruyaert et al . 2020). Horses are frequently led and mounted from the left, and it is possible that asymmetry in the rider’s hands and seat could introduce a level of asymmetry within the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst acknowledging that none of the techniques for local anaesthesia of the proximal metacarpal and metatarsal regions is specific, the authors (Pezzanite et al 2020) make an assumption that 60% improvement in lameness is sufficient. We would challenge this and suggest that with primary proximal suspensory injuries, we would expect to observe at least 90% improvement in lameness in forelimbs (Gruyaert et al 2020) and ≥80% improvement in lameness in hindlimbs (Dyson and Murray 2012), with residual lameness being abolished by ulnar or tibial nerve blocks in forelimbs and hindlimbs, respectively. The need to add ulnar or tibial nerve blocks would also prompt careful ultrasonographic assessment for the detection of possible adhesions between the suspensory ligament and adjacent osseous and soft tissue structures (Dyson et al 2017(Dyson et al , 2018, and assessment of the accessory ligament of the suspensory ligament (Dyson 2014), the accessory ligament of the deep digital flexor tendon (Dyson 2012;Plowright and Dyson 2015) and in hindlimbs, the lateral digital flexor tendon (Davis et al 2014).…”
mentioning
confidence: 99%
“…We therefore advocate that radiographic and ultrasonographic evaluation of the carpus and proximal metacarpal region or tarsus and proximal metatarsal region should be performed routinely after apparently localising pain causing lameness to the proximal metacarpal or metatarsal regions (Dyson 2018b). We also recommend that if a proximal suspensory ligament lesion is identified, the suspensory ligament should be examined in its entirety, because concurrent suspensory ligament branch injuries may coexist, despite an absence of detectable improvement after palmar (plantar) and palmar metacarpal (plantar metatarsal) nerve blocks in the distal third of the metacarpal (metatarsal) region (the so-called 'low-4-point' block) (Marneris and Dyson 2014;Gruyaert et al 2020). We have also observed, as in the report by Pezzanite et al (2020), that some horses with pain originating in the condyles of the third metacarpal bone may have lameness which is not abolished by a 'low-4-point' block, but lameness resolves after perineural analgesia of the palmar metacarpal nerves just distal to the carpus (Dyson 2013b).…”
mentioning
confidence: 99%
See 1 more Smart Citation